Schizophrenia and complications of pregnancy and labor: an individual patient data meta-analysis. - Geddes, J; Verdoux, H; Takei, N; Lawrie, S; Bovet, P; Eagles, J; Heun, R; McCreadie, R; McNeil, T; O'Callaghan, E; Stöber, G; Willinger, U; et al. (1999)
Several epidemiological studies have reported an association between complications of pregnancy and delivery and schizophrenia, but none have had sufficient power to examine specific complications that, individually, are of low prevalence. We, therefore, performed an individual patient meta-analysis using the raw data from case control studies that used the Lewis-Murray scale. Data were obtained from 12 studies on 700 schizophrenia subjects and 835 controls. There were significant associations between schizophrenia and premature rupture of membranes, gestational age shorter than 37 weeks, and use of resuscitation or incubator. There were associations of borderline significance between schizophrenia and birthweight lower than 2,500 g and forceps delivery. There was no significant interaction between these complications and sex. We conclude that some abnormalities of pregnancy and delivery may be associated with development of schizophrenia. The pathophysiology may involve hypoxia and so future studies should focus on the accurate measurement of this exposure.